HISTORICAL-LEGAL ANALYSIS OF LEGAL ANTHROPOLOGY AS A METHODOLOGY TO STUDY RIGHTS OF A HUMAN AND A CITIZEN - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: anthropological principles of human rights in the legal field in order to substantiate and establish the humanistic nature of law in the context of the principles of democracy implementation have been analyzed in the paper. Methods: phenomenological; hermeneutic; comparative-legal; sociological; logical; dialectical. Results: the nature and a place of the category of «legal anthropology» have been clarified, concept of «a human and law» content problems have been considered, attention has been paid to the fact that legal anthropology is a multidisciplinary sphere of knowledge about the interrelation between a human and law. Discussion: approaches to the correlation of a human and law problem that content have been determined by the recognition of a human as the highest social value, the form of reflection and the way of moral principles in social relations embodiment. The historiographical review of the problems of legal anthropology studies reflects the multidimensional nature of its problems and attempts to resolve them, and demonstrates that legal anthropology has its own history and tradition. Being born among other disciplines, legal anthropology develops as an integrated, interdisciplinary scientific direction, which explores law on the basis of anthropological approach. At the same time, the content that various researchers have contained and still contain in the concept of anthropological approach and anthropology is different. The historiographic review of the problems of legal anthropology confirms its multidimensionality and raises a question of its system. A systematic review of the problems of legal anthropology, which aims to generalize the issues of its research, offers its multidimensional. Anthropological principles of human rights in the legal field in order to substantiate and establish the humanistic nature of law in the context of the principles of democracy implementation have been analyzed in the paper. The nature and a place of the category of «legal anthropology» have been clarified, concept of «a human and law» content problems have been considered, attention has been paid to the fact that legal anthropology is a multidisciplinary sphere of knowledge about the interrelation between a human and law. The approaches to the correlation of a human and law problem that content have been determined by the recognition of a human as the highest social value, the form of reflection and the way of moral principles in social relations embodiment.